Exploring university- industry experience in education and employability of Nigerian graduates - Aloysius, Odigbo Ikechukwu (2019)
The importance of university education lies in the development of certain skills in the areas of knowledge and learning that provides a basic understanding approach with regard to industrial production. The main aim and objective of this study are based on the experience of university-industry in education and employability among Nigerian graduates is a concern about skills, knowledge and characteristics that will help students /graduates gain employment. Employability skills are the transferable core skills that individuals need to make them work. The purpose of this study is based on Nigerian employers and industries that are increasingly driving the university to focus more on employability skills to improve the performance of graduates. This study reviews various literature and interviews, collective expert voice, industry employer experience, university professional and academic opinions, on how to develop and improve employment skills among Nigerian graduates. The study decided to select participants and field of study where they were informed about the problems of the study and control phenomena have also been investigated. The study uses qualitative descriptive methods, employing twelve participants in target groups such as four members comprising graduates who have worked, four deans of faculty members at the university (Nnamdi Azikiwe University Awka, Anambra State) and four industry managers (Nigeria Breweries). This study uses interviews, documents, and observations as a primary source of data collection. However, this study shows that the skills sought in the industry are communication skills such as writing assignments and reports, presentation of reports or assignments in the classroom, and customer service tasks, teamwork such as working with others in the main task area, as well as in solving problems such as technological skills such as computerized skills, information technology skills, and workplace training, leadership skills, diligence and motivation, ability to work in stressful situations, self-esteem, analytical skills, creativity and positive attitude. In addition, the findings show the Student Industrial Work Experience Scheme (SIWES) or Industrial Training (IT), workplace training, workshops, induction and training exercises aimed at providing both graduates and students to be familiar with industrial work and gain efficiency. Therefore, studies show that there is a link between university and industry in Nigeria through partnerships in industrial development training and entrepreneurial development training, but a lack of stakeholder co-operation and coordination. Undoubtedly, this study shows that universities design and develop employability skills in their curriculum to improve the performance of graduates in industrial work activities if they are employed. In most cases, employability development has no practical support and largely theoretical, not practicing because of government political instability. In addition, this study identified the challenges facing Nigerian universities on their graduates' employability as insufficient funding to conduct research, poor infrastructure, crowded classrooms, inconsistent energy supplies, for example, electricity for using internet facilities, poor library facilities, as lack of improvements in information technology. Therefore, this study suggests that universities should make their teaching more practical-oriented, allowing students to participate in more extracurricular activities, inviting hiring managers from the IT industry to conduct interactive sessions with students, developing employability skills and upgrading at universities curriculum, organizing discussion sessions between soft skills teachers and IT industry recruitment managers, which have sufficient linkages between universities and industries to enhance graduate work experience. Finally, the study suggests that universities should engage in employment or open employment centres within the university in collaboration with industrial management. Universities should coordinate and promote academic activities; backing up; make changes, review their curriculum and academia related to other stakeholders and participate in various industries.